Einstein Operations of Fuzzy Matrices - M. Selvarajan, T.; Sriram, S.; S. Ramya, R. (International Journal of Engineering and Technology, 2018)
In this paper, the authors defined the Einstein operations of fuzzy matrices, intuitionistic fuzzy matrices and proved several properties of them.Â Â